The development of the common fraction concept in grade three learners - Fraser, Claire Anne (Rhodes University, Faculty of Education, Department of Education, 2001)
Over a period of nine months in 1999, a longitudinal teaching intervention was undertaken with Grade 3 learners in the Fort Beaufort district, Eastern Cape. Working in the interpretive paradigm, the intervention focussed on: - the development of the common fraction concept, - the relevance of the hierarchy of Murray and Olivier's Four Levels of Development in common fractions and - whether learners' informal knowledge could be utilised in developing this concept. Using the Problem-centred approach to teaching mathematics, problems set in reallife contexts were used as vehicles for learning. Learners were required to discuss, reflect and make sense of the mathematics they were doing. Participant observation, completed worksheets and unstructured interviews with learners, formed the primary method of data collection. Learners' work was analysed and classified according to the method used and manner in which the solution was notated. Results showed that learners were able to achieve a significant degree of success in developing a stable common fraction concept. Learners were afforded opportunities to construct their own ideas and to develop a deeper understanding of the concept. Many methods used were based on their informal knowledge of sharing. Learners made sense of realistic problems using drawings, and invented their own procedures. Apart from Level One, Phase Three, all Murray and Olivier's Levels of Development could be identified during the research. This study will provide educators with valuable information on how learners solve mathematical problems involving fractions and how informal knowledge can be used as a foundation on which to build.
Keywords: Mathematics -- Study and teaching (Elementary); Mathematics -- Problems, exercises, etc; Fractions -- Study and teaching (Elementary)